Pengaruh Ekstrak Kulit Buah Mangga Harum Manis (Mangifera indica L) terhadap Tekanan Darah pada Tikus Putih Jantan Hipertensi - Ifmaily, Ifmaily (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2019)
Hypertension is the most common disease in Indonesia. The impact of hypertension can affect other organs such as the kidneys, heart, and eventually cause death. The prevalence of hypertension increases from year to year. One alternative treatment for hypertension is the use of natural ingredients that contain flavonoids. Mango (the leaves, fruit, fruit peel and stems) is one of the plants that can be used for anti-hypertension, because of its flavonoid content. Ethanol extract of leaves, fruit and stem of Mango already proved as an antihypertensive drug, but the peel of the fruit has not been studied, so far it has only been a waste. The purpose of this study was to determine the effect of varying doses of the extract of mango peel varieties Harum Manis (EKBMHM) on white male hypertensive rats. This study was experimental with a pretest-posttest control group design, using male white rats, divided into 6 groups: negative control group, positive control, treatment group 30 mg / kg BW, treatment group 60 mg / kg BW, treatment group 120 mg / kg BW and comparison group (amlodipine 5 mg / kgBW. Prednisone 1.5 mg / kgBW in 2.5% NaCl are used to induce hypertension in animal. The parameters used were blood pressure which measured using a Non-Invasive Blood Pressure. Data analysis was calculated using one-way ANOVA followed by Duncan's test. The results obtained showed a dose of 30 mg / kg BW and a dose of 120 mg / kg BW extract of mango peel cannot reduce blood pressure, while a dose of 60 mg / kg BW can reduce blood pressure in hypertensive rats where the results of blood pressure measurements are not significantly different with comparison group (amlodipine 5 mg / kg BW). The conclusion for this research,the administration of mango peel varieties Harum Manis extract at a dose of 60 mg / kg BW given to hypertensive rats shows potential as an antihypertensive drug (p value = 0.047).